Laser-Fabricated Micro/Nanostructures: Mechanisms, Fabrication Techniques, and Applications - Andrei Teodor Matei; Anita Ioana Visan; Irina Negut (Micromachines)
The rapid evolution of optoelectronic devices necessitates innovative fabrication techniques to improve their performance and functionality. This review explores the advancements in laser processing as a versatile method for creating micro- and nanostructured surfaces, tailored to enhance the efficiency of optoelectronic applications. We begin by elucidating the fundamental mechanisms underlying laser interactions with materials, which facilitate the precise engineering of surface topographies. Following this, we systematically review various micro/nanostructures fabricated by laser techniques, such as laser ablation, laser-induced periodic surface structures (LIPSS), and two-photon polymerization, highlighting their unique properties and fabrication parameters. The review also delves into the significant applications of these laser-fabricated surfaces in optoelectronic devices, including photovoltaics, photodetectors, and sensors, emphasizing how tailored surface structures can lead to improved light absorption, enhanced charge carrier dynamics, and optimized device performance. By synthesizing current knowledge and identifying emerging trends, this work aims to inspire future research directions in the design and application of laser-fabricated micro/nanostructures within the field of optoelectronics. Our findings underscore the critical role of laser technology in advancing the capabilities of next-generation optoelectronic devices, aligning with the scope of emerging trends in device engineering.